Meningkatkan Keterampilan Berbicara dan Hasil Belajar Materi Menyampaikan Informasi dengan Metode Cerita Berantai Siswa Kelas 6 SDN 2 Sumberanyar Kecamatan Jatibanteng, Situbondo - Syahri, Mokh (Jurnal Simki Pedagogia, 2023)
The problem to be studied in this action research is that the use of the chain story method can improve speaking skills and the results of Indonesian language learning materials conveying information to grade 6 students at SDN 2 Sumberanyar, Jatibanteng District. The purpose of the research to be obtained is to find out the improvement in speaking skills and the results of learning Indonesian in the material for conveying information to grade 6 students at SDN 2 Sumberanyar, Jatibanteng sub-district, applying the chain story method. This study used two rounds of action research. Each round consists of four stages, namely design, activity, observation, reflection and revision. The targets of this research were grade 6 students at SDN 2 Sumberanyar, Jatibanteng District, for the 2022/2023 academic year. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student learning outcomes increased from cycle I to cycle II, namely, cycle I (57.14%), cycle II (100%). The conclusion from this study is that learning the chain story method can have a positive effect on improving speaking skills and learning outcomes for grade 6 students at SDN 2 Sumberanyar, Jatibanteng District, in the 2022/2023 academic year, and this learning can be used as an alternative to learning Indonesian.